The Implementation of Classroom-Based Character Education in Elementary School Learning - Fathurrohman; Suparlan; Hendra Prasetia; Nurhayati (The Indonesian Institute of Science and Technology Research, 2026)
This study examines the implementation of classroom-based character education in an elementary school setting. Using a qualitative exploratory case study design, the research was conducted at Muhammadiyah Karangkajen Elementary School in Yogyakarta. The participants included the principal, teachers, and students selected through purposive sampling. Data were collected through interviews, observations, and document analysis, with the researchers serving as key instruments supported by interview and observation guides. Data were analyzed through coding, thematic categorization, and interpretative analysis. The findings reveal that classroom-based character education is implemented through four dimensions: integration of character values into curriculum and learning activities, structured classroom management practices, student-centered learning models such as PBL, CTL, inquiry, cooperative learning, and discovery learning, and the development of local content. The local content component is explicitly reflected in Javanese language instruction and batik-making activities, which foster manners, respect, responsibility, independence, and cooperation among students.